The Predictive Ability of Social Anxiety within Internet Addiction among University Students - ALHarbi, Bassam Hilal; Al-Mehsin, Salama Aqeel; Al-Rababaah, Jaafar Kamel; Abdel-Al Ibrahim, Khaled Ahmed (Journal of Education and e-Learning Research, 2021)
The study aimed to identify the predictive ability of social anxiety in Internet addiction among university students, by relying on the relational descriptive approach. The study sample consisted of (462) male and female students from the Faculty of Educational Sciences at the Hashemite University who were selected through the available random method and were assessed by the social anxiety scale and the Internet addiction scale prepared by Young (1997) which was modified by Widyanto and McMurran (2004) after confirming the appropriateness of its psychometric properties. The study results found that social anxiety level and Internet addiction level were high among the study sample and indicated a statically significant correlation at level (0.01) between the social anxiety level and the level of Internet addiction, which indicates that the higher the social anxiety level, the higher the internet addiction level and that social anxiety works as a predictor of the internet addiction. Results also indicated a nonexistence of statistically significant differences in the social anxiety level as well as the level of Internet addiction due to gender. The current study recommended the activation of students’ counseling services for students within the university and society as a whole to train them on controlling and self-control, which reduce the social anxiety and increase the university’s interest about Internet addiction phenomenon in addition to holding awareness programs to help solve problems of this phenomenon.